Composite sodium supplementing agent, sodium ion battery positive plate and preparation method of sodium ion battery positive plate
By using a composite sodium supplement agent, combining alkaline and acidic sodium salts, the gel phenomenon and low energy density caused by the positive sodium supplement agent of existing sodium ion batteries are solved, and high energy density and good cycle stability are achieved.
Patent Information
- Application Number
- CN202510147406.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing sodium-ion battery positive electrode sodium supplementation agents such as sodium oxalate, etc., will destroy the binder, resulting in uneven dispersion of the positive electrode slurry, affecting the battery process, and the addition of a large amount of oxalic acid will occupy the space of the active substance and reduce the battery energy density.
Compound sodium supplementation agents are used, including 10%~30% alkaline sodium supplementation agents and 70%~90% acidic sodium salts by neutralizing the alkalinity of alkaline sodium supplementation agents by acidic sodium salts, the use of oxalic acid is avoided, the positive electrode preparation process is optimized, and the energy density of the battery is improved.
The gel phenomenon is effectively avoided, and the first coulomb efficiency and cycle stability of sodium ion batteries are improved. The first coulomb efficiency can reach 90.9%, and the capacity retention rate can reach 98.4% for 500 weeks of cycle.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a composite sodium supplement, a sodium ion battery positive electrode sheet and a preparation method thereof. Background Art
[0002] Since the stock of sodium ore is much larger than that of lithium ore, sodium-ion batteries have a huge cost advantage over lithium-ion batteries in the field of energy storage. In addition, sodium-ion batteries have the advantages of milder reaction, higher safety and green environmental protection compared with lithium-ion batteries. However, sodium-ion batteries still have the shortcoming of low energy density, which makes them less competitive than lithium-ion batteries. Supplementing sodium-ion batteries with sodium supplements can effectively improve the initial efficiency of sodium-ion batteries and alleviate battery capacity loss, thus improving the shortcoming of low energy density of sodium-ion batteries.
[0003] However, commonly used positive electrode sodium supplement additives include: sodium oxalate, sodium carbonate, sodium acetate, sodium citrate, etc. These sodium supplement agents are all alkaline substances, which will destroy the binder polyvinylidene fluoride (PVDF), aggravate the gel phenomenon, cause uneven dispersion of the positive electrode slurry, make the positive electrode slurry unable to be coated, and affect the battery process.
[0004] In the prior art, oxalic acid is generally added to neutralize alkaline substances to improve the gel problem of the positive electrode slurry. However, the addition of a large amount of oxalic acid will occupy the space of the active material, thereby reducing the energy density of the battery. In addition, the addition of oxalic acid will increase the production process and cost of the battery. Summary of the invention
[0005] The object of the present invention is to provide a composite sodium supplement, a sodium ion battery positive electrode sheet and a preparation method thereof. When the composite sodium supplement is used to prepare a sodium ion battery positive electrode sheet, the problem that the electrode sheet cannot be prepared due to gel can be avoided without adding oxalic acid, and the prepared sodium ion battery has a high energy density.
[0006] The invention provides a composite sodium supplement, which comprises the following components by mass percentage: 10% to 30% of an alkaline sodium supplement and 70% to 90% of an acidic sodium salt.
[0007] Preferably, the composite sodium supplement comprises the following components: 15% to 20% alkaline sodium supplement and 80% to 85% acidic sodium salt.
[0008] Preferably, the acidic sodium salt is one or more of sodium dihydrogen phosphate and sodium bisulfate.
[0009] Preferably, the alkaline sodium supplement is one or more of sodium carbonate, sodium oxalate, sodium acetate and sodium citrate.
[0010] The present invention also provides a sodium ion battery positive electrode sheet, comprising a positive electrode current collector and an active material coated on the positive electrode current collector, wherein the active material comprises a composite sodium supplement, a positive electrode main material, a conductive agent, a binder and a dispersant.
[0011] Preferably, the mass of the composite sodium supplement is 0.5% to 1.0% of the total mass of the positive electrode main material, the conductive agent and the binder.
[0012] Preferably, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and Ketjen black.
[0013] Preferably, the mass ratio of the positive electrode main material, the conductive agent and the binder is (90-96): (3-5): (1-5).
[0014] The present invention also provides a method for preparing a sodium ion battery positive electrode sheet, comprising the following steps: 1) Mixing the active material and the solvent to obtain a positive electrode slurry; 2) The positive electrode slurry obtained in step 1) is coated on the positive electrode current collector and then dried to obtain a positive electrode sheet for a sodium ion battery.
[0015] Preferably, the solid content of the positive electrode slurry is 60% to 70%, and the coating amount of the positive electrode slurry on the positive electrode current collector is 300 to 400 g / m 2 .
[0016] The present invention provides a sodium ion battery positive electrode composite sodium supplement, which includes the following components by mass percentage: 10% to 30% alkaline sodium supplement and 70% to 90% acidic sodium salt. The present invention compounded the acidic sodium salt and the alkaline sodium supplement in a certain proportion, and supplemented the sodium ions while neutralizing the alkalinity of the alkaline sodium supplement by the acidic sodium salt. When preparing the positive electrode slurry, there is no need to add oxalic acid to adjust the pH, which optimizes the process flow of positive electrode preparation, avoids the electrode preparation caused by severe gelation, and can effectively improve the first coulomb efficiency and cycle stability of the sodium ion battery. The experimental results show that when the composite sodium supplement provided by the present invention is prepared and coated on the positive electrode current collector, there is no severe gelation phenomenon. The first coulomb efficiency of the sodium ion battery assembled from the prepared sodium ion battery positive electrode sheet can reach 90.9%, and the capacity retention rate after 500 cycles can reach 98.4%. DETAILED DESCRIPTION
[0017] The invention provides a composite sodium supplement, which comprises the following components by mass percentage: 10% to 30% of an alkaline sodium supplement and 70% to 90% of an acidic sodium salt.
[0018] In terms of mass percentage, the composite sodium supplement provided by the present invention comprises 10% to 30% of the alkaline sodium supplement, preferably 15% to 20%. In an embodiment of the present invention, the mass content of the alkaline sodium supplement may be 10%, 15% or 20%.
[0019] In the present invention, the alkaline sodium supplement is preferably one or more of sodium carbonate, sodium oxalate, sodium acetate, and sodium citrate, and more preferably sodium carbonate. In the present invention, the alkaline sodium supplement can provide abundant sodium ions and reduce the overall dosage of the sodium supplement. Compared with sodium oxalate, sodium acetate, and sodium citrate, sodium carbonate has a higher sodium ion content at the same addition amount, and has a better sodium supplement effect as an alkaline sodium supplement.
[0020] According to the mass percentage of the composite sodium supplement, the composite sodium supplement provided by the present invention comprises 70% to 90% of acidic sodium salt, preferably 80% to 85%. In an embodiment of the present invention, the mass content of the acidic sodium salt can be 80%, 85% or 90%.
[0021] In the present invention, the acidic sodium salt is preferably one or more of sodium dihydrogen phosphate and sodium bisulfate, and more preferably sodium dihydrogen phosphate. In the present invention, the aqueous solution of the acidic sodium salt is acidic, and no pH regulator needs to be added, which can effectively neutralize the residual alkali in the positive electrode material. , The gel phenomenon that causes the electrode to be unable to be prepared is avoided. The aqueous solutions of sodium dihydrogen phosphate and sodium bisulfate are both acidic and can provide sodium ions. Compared with sodium bisulfate, the phosphate in sodium dihydrogen phosphate can accelerate the migration of sodium ions and achieve a better sodium supplementation effect.
[0022] The present invention has no particular limitation on the preparation method of the composite sodium supplement, and the technical scheme for preparing the composite known to those skilled in the art can be used to achieve uniform mixing of the components.
[0023] The present invention also provides a sodium ion battery positive electrode sheet, comprising a positive electrode current collector and an active material coated on the positive electrode current collector, wherein the active material comprises a composite sodium supplement, a positive electrode main material, a conductive agent, a binder and a dispersant; the composite sodium supplement is the composite sodium supplement described in the above technical solution.
[0024] The sodium ion battery positive electrode sheet provided by the present invention comprises a positive electrode current collector. As an embodiment of the present invention, the positive electrode current collector can be an aluminum foil or a carbon-coated aluminum foil.
[0025] The sodium ion battery positive electrode sheet provided by the present invention also includes an active material coated on the positive electrode current collector, and the active material includes a composite sodium supplement, a positive electrode main material, a conductive agent, a binder and a dispersant.
[0026] In the present invention, the mass of the composite sodium supplement is preferably 0.5% to 1.0% of the total mass of the positive electrode main material, the conductive agent and the binder; as an embodiment of the present invention, the mass of the composite sodium supplement can be 0.6% to 0.9% of the total mass of the positive electrode main material, the conductive agent and the binder, or it can be 0.8%.
[0027] As an embodiment of the present invention, the main material of the positive electrode can be composite sodium iron phosphate 、 One or more of sodium nickel iron manganate, sodium vanadium phosphate, sodium iron pyrophosphate and sodium vanadium fluorophosphate.
[0028] In the present invention, the conductive agent is preferably one or more of conductive carbon black, carbon nanotubes, graphene, and Ketjen black, and more preferably one or more of conductive carbon black and carbon nanotubes; in an embodiment of the present invention, the conductive agent is conductive carbon black and carbon nanotubes. In the present invention, the mass ratio of the conductive carbon black and carbon nanotubes is preferably (0~3):(0~3), more preferably (1~2):(1~2), and most preferably 1:2. In the present invention, the conductive agent can construct a conductive network between the positive electrode material particles, wherein the conductive carbon black and carbon nanotubes have higher conductivity and richer pore structure. During the slurrying process, they can be evenly dispersed around the positive electrode material and filled in the gaps between the positive electrode material particles, further improving the overall conductivity of the electrode sheet and offsetting the decrease in overall conductivity caused by the addition of the composite sodium supplement.
[0029] The present invention has no special limitation on the type of the binder, and commonly used polyvinylidene fluoride (PVDF) can be selected.
[0030] In the present invention, the mass ratio of the positive electrode main material, the conductive agent and the binder is preferably (90-96): (3-5): (1-5), and more preferably (91-95): (3-4): (1-4). In an embodiment of the present invention, the mass ratio of the positive electrode main material, the conductive agent and the binder is 95:3:2.
[0031] In the present invention, there is no particular limitation on the dispersant, and commonly used polyvinyl pyrrolidone (PVP) can be selected.
[0032] In the present invention, the dispersant preferably accounts for 0.1% to 0.5% of the total mass of the positive electrode main material, the conductive agent and the binder, and more preferably 0.3%.
[0033] The present invention also provides a method for preparing the positive electrode sheet of a sodium ion battery according to the above technical solution, comprising the following steps: 1) Mixing the active material and the solvent to obtain a positive electrode slurry; 2) The positive electrode slurry obtained in step 1) is coated on the positive electrode current collector and then dried to obtain a positive electrode sheet for a sodium ion battery.
[0034] The active material of the present invention is mixed with a solvent to obtain positive electrode slurry.
[0035] In the present invention, the solid content of the positive electrode slurry is preferably 60% to 70%, more preferably 61% to 65%; in an embodiment of the present invention, the solid content of the positive electrode slurry is 62%.
[0036] In the present invention, there is no particular limitation on the type of the solvent, and N-methylpyrrolidone (NMP) commonly used in the art can be selected.
[0037] The present invention has no particular limitation on the mixing method, and a stirrer well known to those skilled in the art can be used for uniform mixing.
[0038] After obtaining the positive electrode slurry, the present invention applies the positive electrode slurry to the positive electrode current collector and then dries it to obtain a positive electrode sheet.
[0039] In the present invention, the coating amount of the positive electrode slurry on the positive electrode current collector is preferably 300-400 g / m 2 , more preferably 325~375g / m 2 In an embodiment of the present invention, the coating amount of the positive electrode slurry on the positive electrode current collector is 360g / m 2 .
[0040] The present invention has no special limitation on the type of the positive electrode current collector, and aluminum foil or carbon-coated aluminum foil well known to those skilled in the art can be used.
[0041] As an embodiment of the present invention, the drying temperature can be 100-120° C., or 105-115° C.; the drying time can be 2-10 min, or 4-6 min.
[0042] In the present invention, during the coating process, the coating machine head and the machine tail work simultaneously, and the foil is pulled from the machine head to the machine tail, passing through an oven in the middle, and the drying is carried out in the oven.
[0043] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1 The composite sodium supplement is composed of 15wt% sodium carbonate and 85wt% sodium dihydrogen phosphate.
[0045] Example 1-1 Preparation method of positive electrode sheet: weigh the positive electrode main material composite sodium iron phosphate NFPP, conductive agent conductive carbon black SP, conductive agent carbon nanotube CNT, binder polyvinylidene fluoride PVDF, dispersant polyvinyl pyrrolidone PVP and the composite sodium supplement in Example 1 according to the mass ratio, NFPP:SP:CNT:PVDF=95:1:2:2 (mass ratio), the composite sodium supplement accounts for 0.8% of the total mass of NFPP, SP, CNT, and PVDF, and PVP accounts for 0.3% of the total mass of NFPP, SP, CNT, and PVDF; mix the weighed materials evenly and add N-methylpyrrolidone (NMP) to obtain a positive electrode slurry with a solid content of 62%, and apply the positive electrode slurry to the aluminum foil positive electrode current collector. During the coating process, the coating machine head and the machine tail work simultaneously, and the foil is pulled from the machine head to the machine tail, passing through an oven in the middle, and drying is carried out in the oven. The coating amount is 360g / m 2 The oven is divided into three sections, with temperatures of 106°C, 108°C, and 110°C respectively. The drying time is 5 minutes in total. After rolling, slitting, and die-cutting, the positive electrode sheet is obtained.
[0046] Example 1-2 The difference between Example 1-2 and Example 1-1 is that the composite sodium supplement accounts for 0.5% of the total mass of NFPP, SP, CNT, and PVDF, and the other operating conditions are the same as those of Example 1-1.
[0047] Examples 1-3 The difference between Example 1-3 and Example 1-1 is that the composite sodium supplement accounts for 1.0% of the total mass of NFPP, SP, CNT, and PVDF, and the other operating conditions are the same as those of Example 1-1.
[0048] Examples 1-4 The difference between Example 1-4 and Example 1-1 is that the added amounts of the conductive agent conductive carbon black SP and the conductive agent carbon nanotube CNT are different, NFPP:SP:CNT:PVDF=95:2:1:2 (mass ratio), and the other operating conditions are the same as Example 1-1.
[0049] Examples 1-5 The difference between Example 1-5 and Example 1-1 is that the added amounts of the conductive agent conductive carbon black SP and the conductive agent carbon nanotube CNT are different, NFPP:SP:CNT:PVDF=95:1.5:1.5:2, and the other operating conditions are the same as Example 1-1.
[0050] Examples 1-6 The difference between Example 1-6 and Example 1-1 is that only conductive carbon black SP is added as the conductive agent, NFPP:SP:PVDF=95:3:2 (mass ratio), and the other operating conditions are the same as those of Example 1-1.
[0051] Examples 1-7 The difference between Example 1-7 and Example 1-1 is that only carbon nanotubes CNT are added as the conductive agent, NFPP:CNT:PVDF=95:3:2 (mass ratio), and the other operating conditions are the same as those of Example 1-1.
[0052] Example 2 The difference between Example 2 and Example 1 is that the composite sodium supplement comprises 20 wt % of sodium carbonate and 80 wt % of sodium dihydrogen phosphate.
[0053] Example 2-1 The difference between Example 2-1 and Example 1-1 is that the composite sodium supplement used is the composite sodium supplement in Example 2, and the other operating conditions are the same as those in Example 1-1.
[0054] Example 3 The difference between Example 3 and Example 1 is that the composite sodium supplement comprises: 10 wt % of sodium carbonate and 90 wt % of sodium dihydrogen phosphate.
[0055] Example 3-1 The difference between Example 3-1 and Example 1-1 is that the composite sodium supplement used is the composite sodium supplement in Example 3, and the other operating conditions are the same as those in Example 1-1.
[0056] Comparative Example 1 The difference between Comparative Example 1 and Example 1-1 is that no composite sodium supplement is added, and the other operating conditions are the same as those of Example 1-1.
[0057] Comparative Example 2 The difference between Comparative Example 2 and Example 1-1 is that only sodium carbonate is added as the sodium supplement, and the other operating conditions are the same as those of Example 1-1.
[0058] Comparative Example 3 The difference between Comparative Example 3 and Example 1-1 is that only sodium dihydrogen phosphate is added as the sodium supplement, and the other operating conditions are the same as those of Example 1-1.
[0059] The positive electrode sheet obtained in the above embodiments and comparative examples is laminated with the negative electrode sheet (aluminum foil) and the diaphragm to obtain a sodium battery cell, and then baked, injected, formed, and divided into volumes after being assembled into an aluminum shell to obtain a sodium ion battery, wherein the preparation method of the negative electrode sheet is to disperse hard carbon: SP (carbon black conductive agent): CMC (sodium carboxymethyl cellulose): SBR (styrene butadiene rubber) = 95:2:1.5:1.5 (mass ratio) in deionized water to prepare a negative electrode slurry, and then obtain the negative electrode sheet after coating, rolling, slitting, and die cutting. The diaphragm is a PE ceramic diaphragm, the solvent of the electrolyte is composed of a mixed solution of ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1, and the solute of the electrolyte is 1M sodium hexafluorophosphate (NaPF6).
[0060] Fineness test: Use a scraper fineness meter to test the positive electrode slurry when it is discharged.
[0061] Slurry form: judged based on the slurry fluidity during discharge.
[0062] The calculation method for the first coulombic efficiency is: the first split capacity discharge capacity divided by (the sum of the first formation capacity and the first split capacity charge capacity). The first formation charge capacity is to charge to a certain voltage at 0.2C, and then charge to the cut-off voltage (3.4V) at 0.33C. The sum of these two parts of charge capacity is the first formation charge capacity. The first split capacity discharge capacity is the capacity obtained by discharging to 1.5V at a rate of 0.2C, which is the first split capacity discharge capacity. The use of batteries will go through the two steps of formation and split capacity to ensure the uniformity of the SEI film formed on the negative electrode side of the battery and the consistency of the capacity of different batteries.
[0063] The calculation method of the capacity retention rate after 500 cycles is as follows: the test voltage range is 1.5~3.4V, and then the prepared battery is subjected to constant current charge and discharge test at a rate of 0.5C on a charge and discharge instrument after two steps of formation and capacity separation. After 500 cycles, the ratio of the remaining capacity to the initial 0.5C discharge capacity is the capacity retention rate.
[0064] The performance data of the positive electrode slurry and the sodium ion battery in the examples and comparative examples are shown in Table 1.
[0065] Table 1 Cathode slurry and sodium ion battery performance data
[0066] It can be seen from the above embodiments that the sodium ion battery assembled by using the composite sodium supplement agent to prepare the positive electrode sheet of the sodium ion battery has an initial coulombic efficiency of 87.9% to 90.9%, and a capacity retention rate of 97.5% to 98.4% after 500 cycles. The addition of the composite sodium supplement agent has a higher initial efficiency than that of Comparative Example 1 without the addition of the sodium supplement agent, and at the same time has a better cycle capacity. Compared with Comparative Examples 2 and 3, the use of a single sodium supplement agent has better performance, indicating that the combined use of sodium carbonate and sodium dihydrogen phosphate can further improve the initial efficiency of the battery and extend the battery life.
[0067] The difference between Example 1-2 and Example 1-3 compared to Example 1-1 is the amount of composite additives in the slurry. The results show that the addition of sodium supplements can have a good effect within 0.5%~1.0% of the total mass of the positive electrode main material, conductive agent and binder. Example 2-1 and Example 3-1 explored the different ratios of the two substances in the composite sodium supplement. It can be seen from the results that the addition of the three sodium supplements in Examples 1~3 can have a good effect. The mild gel of Example 2-1 will not affect the electrode preparation. When sodium carbonate accounts for 15% and sodium dihydrogen phosphate accounts for 85%, the composite sodium supplement has the best performance. By adjusting the type and proportion of the conductive agent, Examples 1-5~1-7 found that the performance of the sodium supplement can be maximized when SP and CNT are used in combination, and the ratio of SP:CNT=1:2 used in Example 1-1 has a higher first effect and better cycle capacity.
[0068] In Comparative Example 1, no sodium supplement was added. Due to the residual alkali in the active material itself, the positive electrode slurry showed a certain gel state. At the same time, because no sodium supplement was added, the initial efficiency was relatively low. Compared with Examples 1-1 to 1-7, 2-1, 3-1 and Comparative Example 3, it showed the highest capacity decay after 500 cycles at a current density of 0.5C, which proved that the residue after the decomposition of the sodium supplement was helpful for the formation of the negative electrode SEI film, and could effectively improve the cycle life of the battery.
[0069] In Comparative Example 2, sodium carbonate alone is added as a sodium supplement because it is alkaline. The alkalinity of sodium carbonate further aggravates the gelation phenomenon of the positive electrode slurry, making it impossible to carry out coating and subsequent testing.
[0070] Comparative Example 3 adds sodium dihydrogen phosphate as a sodium supplement to neutralize the residual alkali in the active material and provide some sodium ions to compensate for the consumption during the formation process. However, due to its low sodium ion content, the effect on the first effect is limited. The PO4 2- Ions are beneficial to film formation and improve the cycle performance of the battery.
[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composite sodium supplement, comprising the following components by mass percentage: 10% to 30% alkaline sodium supplement and 70% to 90% acidic sodium salt.
2. The composite sodium supplement according to claim 1, characterized in that It includes the following components: 15%~20% alkaline sodium supplement and 80%~85% acidic sodium salt.
3. The composite sodium supplement according to claim 1 or 2, characterized in that The acidic sodium salt is one or more of sodium dihydrogen phosphate and sodium bisulfate.
4. The composite sodium supplement according to claim 1 or 2, characterized in that The alkaline sodium supplement is one or more of sodium carbonate, sodium oxalate, sodium acetate and sodium citrate.
5. A positive electrode sheet for a sodium ion battery, comprising a positive electrode current collector and an active material coated on the positive electrode current collector, characterized in that: The active material comprises a composite sodium supplement, a positive electrode main material, a conductive agent, a binder and a dispersant, and the composite sodium supplement is the composite sodium supplement according to any one of claims 1 to 4.
6. The sodium ion battery positive electrode sheet according to claim 5, characterized in that: The mass of the composite sodium supplement is 0.5% to 1.0% of the total mass of the positive electrode main material, the conductive agent and the binder.
7. The sodium ion battery positive electrode sheet according to claim 5, characterized in that: The conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and Ketjen black.
8. The sodium ion battery positive electrode sheet according to any one of claims 5 to 7, characterized in that: The mass ratio of the positive electrode main material, the conductive agent and the binder is (90-96): (3-5): (1-5).
9. The method for preparing a positive electrode sheet for a sodium ion battery according to any one of claims 5 to 8, characterized in that: The steps include: 1) Mixing the active material and the solvent to obtain a positive electrode slurry; 2) The positive electrode slurry obtained in step 1) is coated on the positive electrode current collector and then dried to obtain a positive electrode sheet for a sodium ion battery.
10. The preparation method according to claim 9, characterized in that: The solid content of the positive electrode slurry is 60% to 70%, and the coating amount of the positive electrode slurry on the positive electrode current collector is 300 to 400 g / m 2 .
Citation Information
Patent Citations
Sodium-ion battery positive electrode slurry, positive electrode plate, battery and preparation method
CN115663179A
Positive pole piece of sodium-ion battery, preparation method of positive pole piece and sodium-ion battery
CN116364926A
Method for improving first coulombic efficiency and energy density of sodium ion battery, positive electrode slurry, positive electrode plate and sodium ion battery
CN116646460A
Sodium-ion battery positive electrode slurry for improving gel, preparation method of pole piece and pole piece
CN117638039A
Sodium ion battery positive electrode sodium supplementing agent and application thereof
CN118099567A
Cited By
Sodium-supplementing additive, preparation method thereof and application of sodium-supplementing additive in sodium-ion battery
CN120834209A
Composite sodium supplementing agent, preparation method thereof and sodium ion battery positive pole piece
CN121076137A